2018
DOI: 10.1371/journal.pone.0190599
|View full text |Cite
|
Sign up to set email alerts
|

Mucin acts as a nutrient source and a signal for the differential expression of genes coding for cellular processes and virulence factors in Acinetobacter baumannii

Abstract: The capacity of Acinetobacter baumannii to persist and cause infections depends on its interaction with abiotic and biotic surfaces, including those found on medical devices and host mucosal surfaces. However, the extracellular stimuli affecting these interactions are poorly understood. Based on our previous observations, we hypothesized that mucin, a glycoprotein secreted by lung epithelial cells, particularly during respiratory infections, significantly alters A. baumannii’s physiology and its interaction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 88 publications
2
34
1
Order By: Relevance
“…The acquisition of bla OXA-23 but not of bla KPC suggests that A. baumannii may have a preferential affinity to acquire and maintain certain carbapenemases over other. The observed results agree with the observation that bla OXA-like enzymes are frequently found in this species and only a few reports of bla KPC A. baumannii positive isolates were reported in the literature (41, 42). The intl2 gene together with the typical gene cassette array of the class 2 integron In2-7, dfrA1-sat2-aadA1-orfX-ybfA-ybfB-ybgA , was found.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The acquisition of bla OXA-23 but not of bla KPC suggests that A. baumannii may have a preferential affinity to acquire and maintain certain carbapenemases over other. The observed results agree with the observation that bla OXA-like enzymes are frequently found in this species and only a few reports of bla KPC A. baumannii positive isolates were reported in the literature (41, 42). The intl2 gene together with the typical gene cassette array of the class 2 integron In2-7, dfrA1-sat2-aadA1-orfX-ybfA-ybfB-ybgA , was found.…”
Section: Resultssupporting
confidence: 92%
“…To test the role of bacterial predation in A. baumannii the ability of A118 to lyse K. pneumoniae , as well as E. coli was assessed by performing killing assays. A118 was used as predator and VA360 or E. coli MG1655-Rif as preys as previously described (41, 42). We clearly observed that A118 kills VA360 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Infection of polarized A549 human alveolar epithelial cells. A549 cells were polarized and infected with bacteria cultured in LB broth as described previously (45), using 10 6 bacteria/ml, and incubated for 48 h at 37°C in the presence of 5% CO 2 . All polarized cell samples were fixed after 48 h of infection and analyzed by SEM as described previously (44).…”
Section: Methodsmentioning
confidence: 99%
“…These factors can contribute to the pathogen’s overall survival against host immune effectors, however, these are not the only strategies the microbe may use to promote persistence. The persistence state is an evolutionarily adaptive strategy indicated by a change in metabolic profile, latent growth patterns, and has been associated with expression of toxin/antitoxin systems 11 , 12 . Persistence phenotypes are environmentally modulated, therefore, it is important to address changes in bacterial physiology under stress 13 .…”
Section: Introductionmentioning
confidence: 99%